Factors Associated with the Uptake of Antenatal Tetanus Toxoids Containing Vaccine by First-Time Mothers in Nigeria: Findings from the 2018 Nigerian Demographic Health Survey - Imran Morhason-Bello; Yusuf O. Kareem; Ojone Illah; Joshua O. Akinyemi; Rukiyat Abdus-salam; Olatunji Lawal; Oluwasomidoyin Bello; Gbolahan Obajimi; Isaac F. Adewole (Hindawi Limited, 2022)
Background. Maternal and neonatal tetanus remains a public health problem in low-and-middle-income countries despite the increasing investment in tetanus toxoid containing vaccines (TTCV). Nigeria still records fatalities from tetanus, predominantly in women of reproductive age and in newborns. This is largely due to poor access to vaccinations and high rates of unsupervised labour and childbirth. We aim to investigate the antenatal uptake of TTCV and associated factors among first-time pregnant women in Nigeria. Methods. Data obtained from the 2018 Nigeria Demographic Health Survey (NDHS) was used to generate a list of eligible patients who in the last five years had undergone their first childbirth experience. Data was analysed using univariable and multivariable analyses and reported using a 95% confidence interval. Results. A total of 3640 participants were included in the analysis. 59.6% (95% CI, 57.6-61.8) of participants had received at least two doses of TTCV. Uptake of TTCV irrespective of current marital status was independently associated with number of and place of antenatal care. Other factors associated with receiving two doses of TTCV in all participants were ownership of mobile phones and region of residence. Among the currently married participants, wealth quintiles, region of residence, and having a polygamous family were additional associated factors. Conclusion. There was low uptake of the minimal required dosage of TTCV among first-time pregnant women with the lowest uptake in Northern regions relative to Southern regions. We recommend mixed methods studies to further explore the motivation behind TTCV uptake in pregnant women which can help guide future policies and interventions to improve uptake of tetanus immunization in Nigeria.